2005
DOI: 10.1103/physrevlett.94.141601
|View full text |Cite
|
Sign up to set email alerts
|

RParity from the Heterotic String

Abstract: In T-duality invariant effective supergravity with gaugino condensation as the mechanism for supersymmetry breaking, there is a residual discrete symmetry that could play the role of R-parity in supersymmetric extensions of the Standard Model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The conditions under which the universal axion can serve as the Peccei-Quinn axion were examined and it was found that the strong CP problem is avoided for all but the minimal SL(2, Z) version of the T-duality group of the weakly coupled heterotic string. Most compactifications have a larger T-duality group, and from a phenomenological point of view, a larger group is desirable for generating [25] the R-parity of the MSSM. Although our results were obtained using the linear supermultiplet formulation for the dilaton superfield, we expect that they can be reproduced in the chiral multiplet formulation.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions under which the universal axion can serve as the Peccei-Quinn axion were examined and it was found that the strong CP problem is avoided for all but the minimal SL(2, Z) version of the T-duality group of the weakly coupled heterotic string. Most compactifications have a larger T-duality group, and from a phenomenological point of view, a larger group is desirable for generating [25] the R-parity of the MSSM. Although our results were obtained using the linear supermultiplet formulation for the dilaton superfield, we expect that they can be reproduced in the chiral multiplet formulation.…”
Section: Discussionmentioning
confidence: 99%
“…• When combined with U (1) gauge symmetries, T-duality provides [6] a possible mechanism for R-parity or an even stronger discrete symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…While certain R-parity violating operators can exist in isolation with O(1) coefficients, as argued above string models that do not have an intact R-parity tend to allow all such operators at various mass-dimensions in the superpotential. A more satisfying solution is to identify R-parity as a symmetry of the underlying compactification geometry -such as a remnant of a modular symmetry [43]. As the geometry of the compactified space determines the superpotential (both the tree-level and higher-genus terms) it is reasonable to ask the following question:…”
Section: R-paritymentioning
confidence: 99%